Prolonged Early Antibiotic Use and Bronchopulmonary Dysplasia in Very Low Birth Weight Infants - Novitsky, Alexandra; Tuttle, Deborah; Locke, Robert G.; Saiman, Lisa; Mackley, Amy; Paul, David A. (American Journal of Perinatology, 2015)
Objective The objective of the article is to determine if > 48 hours of antibiotic treatment during the 1st week of life is associated with subsequent isolation of bacteria from the endotracheal tube (ETT), and an increased risk of bronchopulmonary dysplasia (BPD).Study Design Retrospective cohort study of very low birth weight infants. Routine weekly surveillance ETT cultures were obtained to monitor bacterial colonization in all intubated infants. Risk factors for BPD were assessed using unadjusted and multivariable analyses.Results In the study sample (n = 906), infants with BPD (n = 182) were more likely to have received > 48 hours antibiotic treatment (31 vs. 14%, p < 0.01) and have a resistant gram-negative bacilli in ETT (7 vs. 2%, p = 0.0001) compared with infants without BPD. Treatment with > 48 hours of antibiotics remained associated with BPD (adjusted odds ratio, 2.2; 95% confidence interval, 1.4–3.5) after controlling for confounding variables.Conclusions Antibiotic duration > 48 hours in the 1st week of life was associated with subsequent BPD and the presence of resistant bacteria in routine ETT cultures.
Keywords: bronchopulmonary dysplasia; antibiotics; endotracheal tube cultures